Digital culture versus pedagogical authority: trends and challenges - Habowski, Adilson Cristiano (2018)
The essay problematizes the crisis of pedagogical authority in times of digital culture.Digital hyperlinks require reciprocal and interdependent recognition to assertpedagogical authority as a condition of possibility for expression and technologicalreeducation, creating forms of cooperative freedom in the reflexive and pluralauthority of pedagogical sense. In this scenario, teachers need to understand andincorporate the new digital languages into the re-education of information, creatingformative and cooperative links, to assert the authority and interrelations ofknowledge in digital culture. The paths covered indicate the need for reconstructiveactions to access technologies and to recreate knowledge, mobilizing a process ofinterpretation about the disruptive impact of digital culture to recover pedagogicalauthority, since without authority, a critical education is not built.